Effects of ignition advance on a dual sequential ignition engine at lean mixture for hydrogen enriched butane usage. (7th June 2019) - Yontar, Ahmet Alper
Abstract: In this study, the effects of ignition advance on dual sequential ignition engine characteristics and exhaust gas emissions for hydrogen enriched butane usage and lean mixture were investigated numerically and experimentally. The main purpose of this study is to reveal the effects of h-butane application in a commercial spark ignition gasoline engine. One cylinder of the commercially dual sequential spark ignition engine was modeled in the Star-CD software, taking into account all the components of the combustion chamber (intake-exhaust manifold connections, intake-exhaust valves, cylinder, cylinder head, piston, spark plugs). Angelberger wall approximation, k-ε RNG turbulence model and G-equation combustion model were used for analysis. In the dual sequential spark ignition, the difference between the spark plugs was defined as 5° CAD. At the numerical analysis; 10.8:1 compression ratio, 1.3 air-fuel ratio, 2800 rpm engine speed, 0.0010 m the flame radius and 0.0001 m the flame thickness were kept constant. The hydrogen-butane mixture was defined as 4%–96% by mass. In the analysis, the optimal ignition advance was determined by the working conditions. In addition, the effects of changes in ignition advance were examined in detail at lean mixture. For engine operating conditions under investigation, it has been determined that the 50° CAD ignition advance from the top dead center is the optimal ignition advance in terms of engine performance and emission balance. It has also been found that the NOx formation rises up as the ignition advance increases. The BTE values were approximately 12.01% higher than butane experimental results. The experimental BTE values for h-butane were overall 3.01% lower than h-butane numerical results. Highlights: The in-cylinder pressure at 50° CAD is about overall 48.80% higher than 10° CAD. As the ignition advance increases, the formation of NOx rises up. The in-cylinder temperature for the 50° CAD is overall 4.99% lower than the 70° CAD. When the ignition advance is decreased, CO formation rises up. The CO2 for 50° CAD is overall 27.70% lower than the 70° CAD.